(untitled) (Journal of Finance, Business and Management Studies, 2021)
The aim of the research is to identify the impacts and outcomes of employee appraisal system on both employees and institutions for the Omani public and private organizations. The quantitative research method has been implemented via a survey approach for employees in both Omani public and private institutions. Data was collected from employees in Omani private and public sector companies. Data was analyzed using SPSS version 25.0. The investigation found that Omani employees are at above medium level of satisfaction towards the “used appraisal techniques” and the “duration of appraisal process” while they have less satisfaction towards the “Methods of appraisal reports” and “The responsible for the preparation of performance reports”. The investigation found high effectiveness of the appraisal systems implemented in their institutions towards the development of personal career of employees and the achievement of the organizations’ objectives.No significant difference found for the impact of implemented performance appraisal system different This study is important for the management of Omani organizations, as it pays the attention to the need to make some improvements in different sides of the currently implemented appraisal systems even in private or public sector organizations.